5th International Conference on Advanced Composite Materials in Bridges and Structures - Editorial, Equipo (Gaceta Instituto de Ingeniería, UNAM; Vol. 1 Núm. 32 (2007): Gaceta del Instituto de Ingeniería UNAM, 2016)
La 5th  International Conference on Advanced Composite Materials in Bridges and Structures se llevó a cabo del 22 al 24 de septiembre en Winnipeg, Manitoba, Canada.